A baseline study on the concentration of trace elements in the surface sediments off Southwest coast of Tamil Nadu, India. (January 2018) - Godson, Prince S.; Magesh, N.S.; Peter, T. Simon; Chandrasekar, N.; Krishnakumar, S.; Vincent, Salom Gnana Thanga
Abstract: Forty two surface sediment samples were collected in order to document baseline elemental concentration along the Southwest coast of Tamil Nadu, India. The elements detected were Manganese (Mn), Zinc (Zn), Iron (Fe), Copper (Cu), Nickel (Ni) and Lead (Pb). The concentration of Fe and Mn was primarily controlled by the riverine input. The source of Pb and Zn is attributed to leaded petrol and anti-biofouling paints. The calculated index (EF, Igeo and CF) suggests that the sediments of the study area are significantly enriched with all elements except Pb. The contamination factor showed the order of Mn > Zn > Fe > Cu > Ni > Pb. The sediment pollution index (SPI) revealed that the sediments belonged to low polluted to dangerous category. The correlation matrix and dendrogram showed that the elemental distribution was chiefly controlled by riverine input as well as anthropogenic activity in the coast. Highlights: The concentration of Fe and Mn is primarily controlled by the riverine input followed by distribution of heavy minerals in the sediments. The enrichment of Pb and Zn was controlled by application of lead petrol and antibiofouling paints. The SPI reveals that sediments belonged to low polluted to dangerous sediments category. A signiﬁcant association was observed between Fe and sand. Silt has a good association with all metals, especially a strong association with Ni as observed in PCA and dendrogram. One way ANOVA results showed that Fe and OC have significant variation among stations.